Prenylated xanthone derivatives : synthesis of structural analogues of α-mangostin and antitumor activity evaluation - Oliveira, Filipa Sameiro de (2012)
Dissertação de mestrado em Química Farmacêutica Industrial, apresentada à Faculdade de Farmácia da Universidade de Coimbra